Earthquake Disaster Risk Assessment in Purworejo District, Central Java Province, Indonesia - Chatarina Muryani; Sorja Koesuma; Pipit Wijayanti (Department of Physics, Sebelas Maret University, 2024)
Purworejo Regency is directly adjacent to the Indian Ocean and is close to the Java subduction, so it is estimated to have a high earthquake risk index. This study aims to analyze the earthquake disaster risk in Purworejo District, Central Java Province, Indonesia. Earthquake risk analysis methods follow Perka BNPB No 02 of 2012, including hazard, vulnerability, and capacity analysis. The disaster risk index combines the disaster, vulnerability, and capacity indexes. The findings of this study reveal the following: (1) 295 villages within Purworejo Regency fall into the high earthquake hazard category, primarily located in the southern region of Purworejo or near the Java subduction zone. (2) The high vulnerability to earthquakes is widespread across almost all villages in Purworejo Regency. The highest concentration of villages with a high vulnerability index is found in Ngombol District (57 villages), Butuh District (41 villages), and Purwodadi District (40 villages). (3) Purworejo Regency exhibits a capacity to cope with earthquakes that are not categorized as low. The majority, comprising 464 villages (93.92%), falls within the middle class, while 30 villages (6.08%) are classified as having a high capacity. (4) Within Purworejo Regency, 117 villages (23.7%) are at a high risk of earthquakes, and 376 villages face a moderate risk. Only one village has a low disaster risk index.